2002
DOI: 10.1093/humrep/17.12.3157
|View full text |Cite
|
Sign up to set email alerts
|

Semen quality and cryopreservation in adolescent cancer patients

Abstract: Semen cryopreservation was possible in most adolescent cancer cases regardless of age or diagnosis. In all cases the quality of the semen was potentially useful for assisted conception procedures. An offer to freeze sperm in all patients aged >12 years should be made. Adequate support and counselling of both the boys and their parents is essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
47
0
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(60 citation statements)
references
References 38 publications
6
47
0
7
Order By: Relevance
“…Teens as young as 12 have the physical capacity and emotional maturity to provide semen samples and should be informed routinely of this option. 39 Yet a survey of over 200 male patients seen in major cancer centers revealed that only half recalled being told about sperm banking. The most common reason (other than having completed all family building at cancer diagnosis) for not banking sperm was not having been informed in time (25% of men who did not bank sperm).…”
Section: Fertility Preservation: the Need For Better Communication Bementioning
confidence: 99%
“…Teens as young as 12 have the physical capacity and emotional maturity to provide semen samples and should be informed routinely of this option. 39 Yet a survey of over 200 male patients seen in major cancer centers revealed that only half recalled being told about sperm banking. The most common reason (other than having completed all family building at cancer diagnosis) for not banking sperm was not having been informed in time (25% of men who did not bank sperm).…”
Section: Fertility Preservation: the Need For Better Communication Bementioning
confidence: 99%
“…All pubertal boys with testis volumes above 10 -12 mL are encouraged to donate a semen sample before cancer therapy (43,44). Alternatively, electro-ejaculation or testicular sperm extraction from a biopsy can be used as a source to retrieve spermatozoa for boys unable to ejaculate (33).…”
Section: Cryopreservation Of Gametesmentioning
confidence: 99%
“…Chez la petite fille, la congelation et la conservation du tissu ovarien peut ~tre proposee. Chez le garcon pubere, des spermatozoides isoles du sperme ou des urines peuvent 6tre congeles [2] alors que la conservation du tissu testiculaire immature n'est actuellement pas proposee dans la majorite des pays chez le gars prepubere.…”
Section: Effet Des Traitements Anti-cancereux Sur La Spermatogeneseunclassified